Combating COVID-19 in Bangladesh: ideal duration of mandatory quarantine period and policy implications. (October 2020) - Ahsan, Atik; Archie, Rownak Jahan; Tidwell, James B
Amid this Covid-19 pandemic, it is crucial to have the best possible estimation for essential quarantine days to mitigate the risk of Coronavirus spread. In this article, we aim to better approximate the mandatory quarantine days based on the available published literature. Our review of scientific publications revealed that 14 days of quarantine is nor enough neither effective in restricting the Coronavirus. Instead of 14 days, one study suggested to imply 21 days of quarantine to completely assure the symptom appearance in infected people. In case of community transmission, as it might take up to 19.9 days to death from the first appearance of symptom in a community, an effective quarantine period to contain the spread of Coronavirus should be a minimum of 40 days. For a densely populated country like Bangladesh, planning effective strategies using available data is crucial to prevent the upcoming second wave of this pandemic.